1999
DOI: 10.1159/000026396
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Counteracts Interferon-Alpha-Induced Anorexia

Abstract: Interferon-α (IFN-α) immunotherapy is associated with significant adverse neurological effects, including anorexia, which can be a limiting factor in immunotherapy. Thus, it is important to develop strategies that could ameliorate IFN-α-induced neurological manifestations without significantly affecting its immunomodulating properties. In this study, we tested the hypothesis that an endogenous feeding-enhancing peptide, neuropeptide Y (NPY), could inhibit IFN-α-induced anorexia in rats. The results show that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…9 Neuropeptide Y blocks cytokine-induced anorexia, and cytokines block neuropeptide Y-induced feeding, that is cytokine-neuropeptide Y interactions are antagonistic. 10,11 The best characterized examples are the NPY-induced inhibition or blockage of anorexia induced by interleukin-1 beta, interferon-alpha, ciliary neurotrophic factor, and leptin. Endogenous cytokine-peptide interactions relevant to feeding control include reciprocal cytokine-leptin-neuropeptide Y-CRH-glucocorticoid interactions.…”
Section: Cytokines Modulate Feeding By Direct Action In the Brainmentioning
confidence: 99%
“…9 Neuropeptide Y blocks cytokine-induced anorexia, and cytokines block neuropeptide Y-induced feeding, that is cytokine-neuropeptide Y interactions are antagonistic. 10,11 The best characterized examples are the NPY-induced inhibition or blockage of anorexia induced by interleukin-1 beta, interferon-alpha, ciliary neurotrophic factor, and leptin. Endogenous cytokine-peptide interactions relevant to feeding control include reciprocal cytokine-leptin-neuropeptide Y-CRH-glucocorticoid interactions.…”
Section: Cytokines Modulate Feeding By Direct Action In the Brainmentioning
confidence: 99%
“…The anorexigenic outcomes of the APR can be mimicked by externally administering inflammatory cytokines to the periphery or CNS, with synergistic effects occurring between cytokines in some cases [78,79,80,81,82,83,84,85,86]. The resultant alterations in feeding behaviours are typically observed as reductions in meal size, duration, and frequency, and longer inter-meal intervals [80,85,87].…”
Section: The Role Of Cytokines In Weight Regulationmentioning
confidence: 99%
“…Inflammatory cytokines, such as IL-1, IL-1, IL-2, IL-6, IL-8, TNF-, and IFNs have been shown to suppress food intake, both individually and synergistically, after peripheral and central administration [342][343][344][345][346][347][348][349][350] 352 showed that rats treated with IL-1 had a reduced total caloric intake, and consumed relatively more carbohydrates and less protein. Taste aversion can also result from cytokine administration but this does not appear to be a major component of anorexic action 336,353 .…”
Section: Cytokines As Mediators Of Anorexiamentioning
confidence: 99%